The Absence of the Arabidopsis Chaperone Complex CAF-1 Produces Mitotic Chromosome Abnormalities and Changes in the Expression Profiles of Genes Involved in DNA Repair - Varas, Javier; Santos, Juan L.; Pradillo, Mónica (Frontiers in Plant Science, 2017)
Chromatin Assembly Factor 1 (CAF-1) is an evolutionary conserved heterotrimeric chaperone complex that facilitates the incorporation of histones H3 and H4 onto newly synthesized DNA. We demonstrate here that the mutant deficient for the large subunit of the complex, fas1-4, and in minor extent, the mutant deficient for the middle subunit, fas2-1, display chromosome abnormalities throughout Arabidopsis mitosis. Among them, we observed multicentromeric chromosomes at metaphase, and chromatid bridges and acentric fragments at anaphase-telophase. 45S rDNA and telomeric sequences were frequently involved in bridges and fragments. Gene expression analysis by real-time qPCR has revealed that several genes related to homologous recombination (HR) and alternative nonhomologous end-joining (aNHEJ) are overexpressed in fas1-4. These results concur with previous studies which have indicated that HR may be involved in the progressive loss of 45S rDNA and telomeres displayed by fas mutants. However, increased expression of PARP1, PARP2, and LIG6 in fas1-4, and the phenotype shown by the double mutant fas1-4 rad51 suggest that aNHEJ should also be responsible for the chromosomal aberrations observed. The activity of different DNA repair pathways in absence of CAF-1 is discussed.